Glass ceramic composition, glass ceramic sintered body, and electronic component

By calcining a glass ceramic composition containing ZrO2, CaTiO3, BaCO3, Al2O3 and a specific proportion of glass at a temperature below 1000°C, the problem of low relative dielectric constant of the glass ceramic sintered body in the prior art is solved, and a glass ceramic sintered body with high relative dielectric constant and Qf value is realized, thereby promoting the miniaturization of electronic components.

CN119768382APending Publication Date: 2025-04-04MURATA MFG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380061324.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-08-08
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The conventional glass-ceramic composition has a low relative dielectric constant of the sintered body calcined at a temperature below 1000°C, which makes it difficult to miniaturize electronic components such as LC filters.

Method used

A glass ceramic composition containing glass of ZrO2, CaTiO3, BaCO3, Al2O3 and a specific ratio was calcined at a temperature below 1000°C to form a glass ceramic sintered body with high relative dielectric constant and Qf value.

Benefits of technology

The relative dielectric constant and Qf value of the glass ceramic sintered body calcined at a temperature below 1000°C are achieved, and the electrostatic capacitance change rate is reduced, thereby promoting the miniaturization of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768382A_ABST
    Figure CN119768382A_ABST
Patent Text Reader

Abstract

A glass ceramic composition comprising: an aggregate and a glass comprising Li2O, MgO, SrO, B2O3, SiO2, and ZnO; the glass ceramic composition contains 9 to 14 wt% of the glass, and contains 80 to 86 wt% of ZrO2, 2 to 6 wt% of CaTiO3, and 1 to 4 wt% of BaCO3 and / or Al2O3 as the aggregate relative to 100 wt% of the glass ceramic composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a glass ceramic composition, a glass ceramic sintered body and an electronic component. Background Art

[0002] For example, Patent Document 1 discloses a glass-ceramic composition that can be calcined at a temperature below 1000°C, and whose sintered body has a low relative dielectric constant, a small temperature coefficient of resonance frequency and a capacitance change before and after a load test, and a high Qf value, electrical insulation reliability and flexural strength. The glass-ceramic composition is used to form a glass-ceramic layer stacked in a multilayer ceramic substrate. The glass-ceramic composition comprises: a first ceramic powder with forsterite as the main component, a second ceramic powder with SrTiO3 and / or TiO2 as the main component, a third ceramic powder with BaZrO3 as the main component, a fourth ceramic powder with SrZrO3 as the main component, and a borosilicate glass powder containing Li2O, MgO, B2O3, SiO2, ZnO, and at least one additional component selected from CaO, BaO and SrO.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2009 / 113475 Summary of the invention

[0006] However, the relative dielectric constant (ε) of the glass ceramic sintered body obtained by calcining the glass ceramic composition described in Patent Document 1 is r Therefore, it is difficult to miniaturize electronic components using this material, including filters such as LC filters.

[0007] The object of the present invention is to solve the above-mentioned problems, and its object is to provide a glass ceramic composition that can be calcined at a temperature below 1000°C, and its sintered body has a high relative dielectric constant and Qf value and a small electrostatic capacitance change rate. In addition, its object is to provide a glass ceramic sintered body with a high relative dielectric constant and Qf value and a small electrostatic capacitance change rate. Furthermore, its object is to provide a glass ceramic layer composed of a glass ceramic sintered body formed by calcining the above-mentioned glass ceramic composition, or an electronic component having a glass ceramic layer composed of the above-mentioned glass ceramic sintered body.

[0008] The present invention in the first embodiment is a glass-ceramic composition comprising: an aggregate and a glass containing Li2O, MgO, SrO, B2O3, SiO2 and ZnO; relative to 100 weight % of the above-mentioned glass-ceramic composition, it comprises 9 weight % to 14 weight % of the above-mentioned glass, and comprises 80 weight % to 86 weight % of ZrO2, 2 weight % to 6 weight % of CaTiO3, and 1 weight % to 4 weight % of at least one of BaCO3 and Al2O3 as the above-mentioned aggregate.

[0009] The present invention in the second embodiment is a glass ceramic sintered body comprising Zr, Ca, Ti, Ba, Li, Mg, Sr, B, Si and Zn, wherein the content of ZrO2 is 80% to 86% by weight, the content of CaTiO3 is 2% to 6% by weight, the content of BaO is 0.78% to 3.14% by weight, the content of Li2O is 0.3% to 1.5% by weight, the content of MgO is 2% to 5% by weight, the content of SrO is 0.5% to 2.5% by weight, the content of B2O3 is 1.5% to 3% by weight, the content of SiO2 is 1% to 3.5% by weight and the content of ZnO is 0.6% to 2% by weight.

[0010] The present invention in the third embodiment is a glass ceramic sintered body comprising Zr, Ca, Ti, Al, Li, Mg, Sr, B, Si and Zn, wherein the content of ZrO2 is 80% to 86% by weight, the content of CaTiO3 is 2% to 6% by weight, the content of Al2O3 is 1% to 4% by weight, the content of Li2O is 0.3% to 1.5% by weight, the content of MgO is 2% to 5% by weight, the content of SrO is 0.5% to 2.5% by weight, the content of B2O3 is 1.5% to 3% by weight, the content of SiO2 is 1% to 3.5% by weight and the content of ZnO is 0.6% to 2% by weight.

[0011] The present invention in the fourth embodiment is a glass ceramic sintered body comprising Zr, Ca, Ti, Ba, Al, Li, Mg, Sr, B, Si and Zn, wherein the content of ZrO2 is 80% to 86% by weight, the content of CaTiO3 is 2% to 6% by weight, the content of BaO is 0.78% to 2.35% by weight, the content of Al2O3 is 1% to 3.01% by weight, the content of Li2O is 0.3% to 1.5% by weight, the content of MgO is 2% to 5% by weight, the content of SrO is 0.5% to 2.5% by weight, the content of B2O3 is 1.5% to 3% by weight, the content of SiO2 is 1% to 3.5% by weight and the content of ZnO is 0.6% to 2% by weight.

[0012] A fifth aspect of the present invention is an electronic component comprising a glass ceramic layer composed of a glass ceramic sintered body obtained by calcining the glass ceramic composition of the first aspect of the present invention.

[0013] The present invention in a sixth aspect is directed to an electronic component including a glass ceramic layer formed of the glass ceramic sintered body of the second to fourth aspects of the present invention.

[0014] According to the present invention, a glass ceramic composition can be provided which can be calcined at a temperature below 1000°C and whose sintered body has a high relative dielectric constant and Qf value and a small rate of change in electrostatic capacitance. In addition, a glass ceramic sintered body can be provided which has a high relative dielectric constant and Qf value and a small rate of change in electrostatic capacitance. Furthermore, a glass ceramic layer composed of a glass ceramic sintered body formed by calcining the above glass ceramic composition, or an electronic component having a glass ceramic layer composed of the above glass ceramic sintered body can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a perspective view showing the appearance of an LC filter as an example of the electronic component according to the fifth or sixth embodiment of the present invention.

[0016] Figure 2 yes Figure 1 The LC filter shown provides an equivalent circuit diagram.

[0017] Figure 3 Will be manufactured Figure 1 The LC filter shown is a perspective view showing an exploded green laminated body as an intermediate product in a firing step. DETAILED DESCRIPTION

[0018] The glass ceramic composition of the present invention, the glass ceramic sintered body and the electronic component are described below. It should be noted that the present invention is not limited to the following configurations and can be appropriately changed within the scope of the gist of the present invention. In addition, the mode in which each preferred configuration described below is combined with a plurality of components also belongs to the present invention.

[0019] [Glass ceramic composition]

[0020] The glass ceramic composition according to the first embodiment of the present invention is a low temperature co-fired ceramic (LTCC) material that can be sintered at a sintering temperature of 1000° C. or less.

[0021] Specifically, the glass-ceramic composition of the first embodiment includes: an aggregate and a glass containing Li2O, MgO, SrO, B2O3, SiO2 and ZnO; relative to 100 weight % of the above-mentioned glass-ceramic composition, it contains 9 weight % to 14 weight % of the above-mentioned glass, and contains 80 weight % to 86 weight % of ZrO2, 2 weight % to 6 weight % of CaTiO3, and 1 weight % to 4 weight % of at least one of BaCO3 and Al2O3 as the above-mentioned aggregate.

[0022] As a result, it is possible to achieve calcination at a temperature below 1000°C, and the relative dielectric constant (hereinafter abbreviated as ε r ) and a glass-ceramic composition with a high Qf value and a small electrostatic capacitance change rate (hereinafter abbreviated as TCC).

[0023] More specifically, it is possible to achieve calcination at a temperature of 1000°C or lower, and the ε of the sintered body is r A glass ceramic composition having a Qf value of 15 or more (e.g., 15.2 to 17.9), a Qf value of 10,000 GHz or more (e.g., 10,000 to 22,000 GHz), and an absolute value of TCC of 75 ppm / °C or less (e.g., -60 to 75 ppm / °C) in a temperature range of -40°C to 85°C.

[0024] By using this material, it is possible to produce electronic components such as a miniaturized LC filter while maintaining low insertion loss.

[0025] It should be noted that TCC and the temperature coefficient of resonant frequency τ f Both represent temperature characteristics, and the following relationship holds.

[0026] TCC = -2(τ f +α)

[0027] Here, α represents the thermal expansion coefficient.

[0028] The glass ceramic composition comprises the above-mentioned components in the form of powder, that is, a first ceramic powder having ZrO2 as a main component, a second ceramic powder having CaTiO3 as a main component, a third ceramic powder having at least one of BaCO3 and Al2O3 as a main component, and a glass powder (borosilicate glass powder) containing Li2O, MgO, SrO, B2O3, SiO2 and ZnO.

[0029] Here, the purpose of adding each aggregate (filler) and glass is as follows.

[0030] ·ZrO2: Increase ε r and Qf value

[0031] ·CaTiO3: Increase εr , adjust TCC (move TCC to the negative side)

[0032] BaCO3 and Al2O3: Improve the acid resistance of the sintered body (inhibit the crystallization of glass and prevent it from becoming ZnO-rich glass with low acid resistance)

[0033] Glass: Low temperature sintering

[0034] If the content of ZrO2 is less than 80 wt%, sometimes r decline.

[0035] If the content of ZrO2 exceeds 86% by weight, the sinterability of the glass ceramic composition may deteriorate.

[0036] The content of ZrO2 is 80 wt% to 86 wt%, preferably 82 wt% to 85 wt%. If the content of ZrO2 is 82 wt% to 85 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.3 or more, and the Qf value is 20000 or more).

[0037] If the content of CaTiO 3 is less than 2% by weight, the sinterability of the glass ceramic composition may deteriorate.

[0038] When the content of CaTiO 3 exceeds 6% by weight, the absolute value of TCC may become high (become larger on the negative side).

[0039] The content of CaTiO3 is 2 wt% to 6 wt%, preferably 4 wt% to 6 wt%. If the content of CaTiO3 is 4 wt% to 6 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.3 or more, and the Qf value is 20000 or more).

[0040] If the content of at least one of BaCO 3 and Al 2 O 3 is less than 1 wt %, the acid resistance of the sintered body may deteriorate.

[0041] If the content of at least one of BaCO3 and Al2O3 exceeds 4 wt%, the Qf value may decrease, the TCC may increase, or the ε r decline.

[0042] The content of at least one of BaCO3 and Al2O3 is 1 wt% to 4 wt%, preferably 1 wt% to 2 wt%. If the content of at least one of BaCO3 and Al2O3 is 1 wt% to 2 wt%, a higher ε r and Qf values ​​(e.g., ε ris 16.3 or more, and the Qf value is 20000 or more).

[0043] If the glass content is less than 9% by weight, sinterability may deteriorate.

[0044] If the glass content exceeds 14% by weight, ε r decline.

[0045] The content of glass is 9 wt % to 14 wt %, preferably 9 wt % to 10 wt %. If the content of glass is 9 wt % to 10 wt %, a higher ε r and Qf values ​​(e.g., ε r is 16.3 or more, and the Qf value is 20000 or more).

[0046] In the above-mentioned glass, the content of Li2O is preferably 3 weight % to 15 weight %, the content of MgO is preferably 20 weight % to 50 weight %, the content of SrO is preferably 5 weight % to 25 weight %, the content of B2O3 is preferably 15 weight % to 30 weight %, the content of SiO2 is preferably 10 weight % to 35 weight %, and the content of ZnO is preferably 6 weight % to 20 weight %.

[0047] If the content of Li2O is less than 3% by weight, the sinterability of the glass ceramic composition may deteriorate.

[0048] When the content of Li2O exceeds 15 wt%, the acid resistance of the sintered body may deteriorate.

[0049] The content of Li2O is preferably 3 wt% to 15 wt%, more preferably 3 wt% to 7 wt%, and more preferably 5 wt%. If the content of Li2O is 3 wt% to 7 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0050] If the content of MgO is less than 20% by weight, the Qf value may decrease.

[0051] When the content of MgO exceeds 50% by weight, a phenomenon in which part of the glass is crystallized, that is, devitrification may occur.

[0052] The content of MgO is preferably 20 wt% to 50 wt%, more preferably 25 wt% to 50 wt%. If the content of MgO is 25 wt% to 50 wt%, a higher ε r and Qf values ​​(e.g., ε ris 16.1 or more, and the Qf value is 18000 or more).

[0053] If the SrO content is less than 5% by weight, devitrification may occur.

[0054] When the content of SrO exceeds 25% by weight, the Qf value may decrease.

[0055] The content of SrO is preferably 5 wt% to 25 wt%, more preferably 5 wt% to 17.5 wt%. If the content of SrO is 5 wt% to 17.5 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0056] If the content of B2O3 is less than 15% by weight, devitrification may occur.

[0057] If the content of B2O3 exceeds 30% by weight, the acid resistance of the sintered body may deteriorate.

[0058] The content of B2O3 is preferably 15 wt% to 30 wt%, more preferably 15 wt% to 20 wt%. If the content of B2O3 is 15 wt% to 20 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0059] If the content of SiO2 is less than 10% by weight, devitrification may occur.

[0060] If the content of SiO2 exceeds 35% by weight, the sinterability of the glass ceramic composition may deteriorate.

[0061] The content of SiO2 is preferably 10 wt% to 35 wt%, more preferably 15 wt% to 25 wt%. If the content of SiO2 is 15 wt% to 25 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0062] When the content of ZnO is less than 6% by weight, the Qf value may decrease.

[0063] When the content of ZnO exceeds 20% by weight, the acid resistance of the sintered body may deteriorate.

[0064] The content of ZnO is preferably 6 wt% to 20 wt%, more preferably 6 wt% to 9 wt%, and more preferably 7.5 wt%. If the content of ZnO is 6 wt% to 9 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0065] [Glass ceramic sintered body]

[0066] The glass ceramic sintered body of the second embodiment of the present invention contains Zr, Ca, Ti, Ba, Li, Mg, Sr, B, Si and Zn, the content of ZrO2 is 80 weight% to 86 weight%, the content of CaTiO3 is 2 weight% to 6 weight%, the content of BaO is 0.78 weight% to 3.14 weight%, the content of Li2O is 0.3 weight% to 1.5 weight%, the content of MgO is 2 weight% to 5 weight%, the content of SrO is 0.5 weight% to 2.5 weight%, the content of B2O3 is 1.5 weight% to 3 weight%, the content of SiO2 is 1 weight% to 3.5 weight%, and the content of ZnO is 0.6 weight% to 2 weight%.

[0067] The glass ceramic sintered body involved in the third embodiment of the present invention contains Zr, Ca, Ti, Al, Li, Mg, Sr, B, Si and Zn, the content of ZrO2 is 80 weight% to 86 weight%, the content of CaTiO3 is 2 weight% to 6 weight%, the content of Al2O3 is 1 weight% to 4 weight%, the content of Li2O is 0.3 weight% to 1.5 weight%, the content of MgO is 2 weight% to 5 weight%, the content of SrO is 0.5 weight% to 2.5 weight%, the content of B2O3 is 1.5 weight% to 3 weight%, the content of SiO2 is 1 weight% to 3.5 weight%, and the content of ZnO is 0.6 weight% to 2 weight%.

[0068] The glass ceramic sintered body of the fourth embodiment of the present invention contains Zr, Ca, Ti, Ba, Al, Li, Mg, Sr, B, Si and Zn, the content of ZrO2 is 80 weight% to 86 weight%, the content of CaTiO3 is 2 weight% to 6 weight%, the content of BaO is 0.78 weight% to 2.35 weight%, the content of Al2O3 is 1 weight% to 3.01 weight%, the content of Li2O is 0.3 weight% to 1.5 weight%, the content of MgO is 2 weight% to 5 weight%, the content of SrO is 0.5 weight% to 2.5 weight%, the content of B2O3 is 1.5 weight% to 3 weight%, the content of SiO2 is 1 weight% to 3.5 weight% and the content of ZnO is 0.6 weight% to 2 weight%.

[0069] According to the glass ceramic sintered bodies of the second to fourth embodiments, it is possible to realize a glass ceramic sintered body having a high relative dielectric constant and a high Qf value and a small capacitance change rate.

[0070] More specifically, we can achieve r A glass ceramic sintered body having a Qf value of 15 or more (e.g., 15.2 to 17.9), a Qf value of 10,000 GHz or more (e.g., 10,000 to 22,000 GHz), and an absolute value of TCC of 75 ppm / °C or less (e.g., -60 to 75 ppm / °C) in a temperature range of -40°C to 85°C.

[0071] By using this material, it is possible to produce electronic components such as a miniaturized LC filter while maintaining low insertion loss.

[0072] The glass ceramic sintered bodies of the second to fourth embodiments can be produced by calcining the glass ceramic composition of the first embodiment at a temperature below 1000° C. Therefore, the purpose of adding each component in the glass ceramic sintered bodies of the second to fourth embodiments, the critical significance of the content, the preferred range, etc. are the same as those described in the glass ceramic composition of the first embodiment, and therefore, the description here is omitted.

[0073] Among them, regarding BaCO3, since it exists in the form of BaO after calcination, its content is reduced only by the amount of CO2.

[0074] Therefore, in the glass ceramic sintered body of the second embodiment of the present invention, the content of BaO is 0.78 wt% to 3.14 wt%, preferably 0.78 wt% to 1.56 wt%. If the content of BaO is 0.78 wt% to 1.56 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.3 or more, and the Qf value is 20000 or more).

[0075] In the glass ceramic sintered body of the third embodiment of the present invention, the content of Al2O3 is 1 wt% to 4 wt%, preferably 1 wt% to 2 wt%. If the content of Al2O3 is 1 wt% to 2 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.3 or more, and the Qf value is 20000 or more).

[0076] In the glass ceramic sintered body of the fourth embodiment of the present invention, the content of BaO is 0.78 wt% to 2.35 wt%, preferably 0.78 wt% to 1.56 wt%, more preferably 0.78 wt% to 1.5 wt%, and more preferably 0.78 wt%, and the content of Al2O3 is 1 wt% to 3.01 wt%, preferably 1 wt% to 2 wt%, more preferably 1 wt% to 1.5 wt%, and more preferably 1 wt%. If the content of BaO is 0.78 wt% to 1.56 wt% and the content of Al2O3 is 1 wt% to 2 wt%, a higher ε can be achieved. r and Qf values ​​(e.g., ε r is 16.3 or more, and the Qf value is 20000 or more).

[0077] In the glass ceramic sintered bodies according to the second to fourth embodiments of the present invention, the content of each glass component and its preferred range are as follows.

[0078] The content of Li2O is 0.3 wt% to 1.5 wt%, preferably 0.3 wt% to 0.7 wt%, and substantially preferably 0.5 wt%. If the content of Li2O is 0.3 wt% to 0.7 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0079] The content of MgO is 2 wt% to 5 wt%, preferably 2.5 wt% to 5 wt%. If the content of MgO is 2.5 wt% to 5 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0080] The content of SrO is 0.5 wt% to 2.5 wt%, preferably 0.5 wt% to 1.75 wt%. If the content of SrO is 0.5 wt% to 1.75 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0081] The content of B2O3 is 1.5 wt% to 3 wt%, preferably 1.5 wt% to 2 wt%. If the content of B2O3 is 1.5 wt% to 2 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0082] The content of SiO2 is 1 wt% to 3.5 wt%, preferably 1.5 wt% to 2.5 wt%. If the content of SiO2 is 1.5 wt% to 2.5 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0083] The content of ZnO is 0.6 wt% to 2 wt%, preferably 0.6 wt% to 0.9 wt%, and substantially preferably 0.75 wt%. If the content of ZnO is 0.6 wt% to 0.9 wt%, a higher ε r and Qf values ​​(e.g., ε r is 16.1 or more, and the Qf value is 18000 or more).

[0084] In the glass ceramic sintered bodies of the second to fourth embodiments, the glass containing Li2O, MgO, SrO, B2O3, SiO2 and ZnO usually exists in the form of an amorphous phase, and ZrO2, CaTiO3, BaO and Al2O3 usually exist in the form of ceramic powder, i.e., a granular crystalline phase.

[0085] It should be noted that in the glass-ceramic sintered body of the present invention, the glass and other components (aggregates) can be distinguished or separated by analyzing the electron diffraction pattern in a scanning electron microscope (SEM) or a transmission electron microscope (TEM), or by partially dissolving the glass with hydrogen fluoride or the like.

[0086] By performing elemental analysis such as wavelength dispersive X-ray analysis (WDX), energy dispersive X-ray analysis (EDX), and inductively coupled plasma emission spectrometry (ICP) on the distinguished or separated glass and other components, the composition (content) of the glass and other components can be determined in the form of the above-mentioned oxides.

[0087] That is, the glass ceramic sintered body of the second embodiment of the present invention has the same meaning as a glass ceramic sintered body comprising 80 weight % to 86 weight % of Zr calculated as ZrO2, 2 weight % to 6 weight % of Ca and Ti calculated as CaTiO3, 0.78 weight % to 3.14 weight % of Ba calculated as BaO, 0.3 weight % to 1.5 weight % of Li calculated as Li2O, 2 weight % to 5 weight % of Mg calculated as MgO, 0.5 weight % to 2.5 weight % of Sr calculated as SrO, 1.5 weight % to 3 weight % of B calculated as B2O3, 1 weight % to 3.5 weight % of Si calculated as SiO2, and 0.6 weight % to 2 weight % of Zn calculated as ZnO.

[0088] The glass ceramic sintered body of the third embodiment of the present invention has the same meaning as a glass ceramic sintered body comprising 80 wt% to 86 wt% of Zr calculated as ZrO2, 2 wt% to 6 wt% of Ca and Ti calculated as CaTiO3, 1 wt% to 4 wt% of Al calculated as Al2O3, 0.3 wt% to 1.5 wt% of Li calculated as Li2O, 2 wt% to 5 wt% of Mg calculated as MgO, 0.5 wt% to 2.5 wt% of Sr calculated as SrO, 1.5 wt% to 3 wt% of B calculated as B2O3, 1 wt% to 3.5 wt% of Si calculated as SiO2, and 0.6 wt% to 2 wt% of Zn calculated as ZnO.

[0089] The glass ceramic sintered body of the fourth embodiment of the present invention has the same meaning as a glass ceramic sintered body comprising 80 wt% to 86 wt% of Zr calculated as ZrO2, 2 wt% to 6 wt% of Ca and Ti calculated as CaTiO3, 0.78 wt% to 2.35 wt% of Ba calculated as BaO, 1 wt% to 3.01 wt% of Al calculated as Al2O3, 0.3 wt% to 1.5 wt% of Li calculated as Li2O, 2 wt% to 5 wt% of Mg calculated as MgO, 0.5 wt% to 2.5 wt% of Sr calculated as SrO, 1.5 wt% to 3 wt% of B calculated as B2O3, 1 wt% to 3.5 wt% of Si calculated as SiO2, and 0.6 wt% to 2 wt% of Zn calculated as ZnO.

[0090] In the glass ceramic sintered bodies of the second to fourth embodiments, a part of the glass may be crystallized (aggregated), or a part of the ceramic powder may be melted and introduced into the amorphous phase of the glass.

[0091] In addition, in the glass ceramic sintered body of the present invention, MgO and SiO2 can be partially reacted by calcination and exist in the form of Mg2SiO4 (forsterite) (refer to the following reaction formula (1)). In this case, the content of Mg2SiO4 measured by the above method is converted into the content of MgO and SiO2, respectively, and is regarded as a glass ceramic sintered body containing the converted content of MgO and SiO2.

[0092]

[0093] [Electronic components]

[0094] An electronic component according to a fifth embodiment of the present invention includes a glass ceramic layer composed of a glass ceramic sintered body obtained by firing the glass ceramic composition according to the first embodiment.

[0095] An electronic component according to a sixth embodiment of the present invention includes a glass ceramic layer formed of the glass ceramic sintered body according to the second to fourth embodiments.

[0096] Therefore, a miniaturized electronic component can be realized.

[0097] It should be noted that the electronic component of the sixth embodiment only needs to include a glass ceramic layer composed of a glass ceramic sintered body of at least one of the second to fourth embodiments. For example, it may include only a glass ceramic layer (which may be a single layer or multiple layers) composed of a glass ceramic sintered body of any one of the second to fourth embodiments. In addition, it may include a multi-layer glass ceramic layer composed of glass ceramic sintered bodies of two or more different embodiments of the second to fourth embodiments.

[0098] Specific examples of the electronic component are not particularly limited, but filters such as a bandpass filter are preferred, and an LC filter is particularly preferred.

[0099] Figure 1 It is a perspective view showing the appearance of an LC filter as an example of the electronic component according to the fifth or sixth embodiment of the present invention. Figure 2 yes Figure 1 The LC filter shown provides an equivalent circuit diagram. Figure 3 Will be manufactured Figure 1 The LC filter shown is a perspective view showing an exploded green laminated body as an intermediate product in a firing step.

[0100] like Figure 1 As shown, the LC filter 21 includes a component body 23 which is a laminated structure having a plurality of laminated glass ceramic layers, and on the outer surface of the component body 23, terminal electrodes 24 and 25 are provided at each end, and terminal electrodes 26 and 27 are provided in the middle of each side surface.

[0101] like Figure 2 As shown, the LC filter 21 includes two inductors L1 and L2 connected in series between terminal electrodes 24 and 25 , and a capacitor C is formed between a connection point between the inductors L1 and L2 and the terminal electrodes 26 and 27 .

[0102] Reference Figure 3 The green laminate 22 includes a plurality of laminated ceramic green sheets 28 to 40 which become the component body 23 by firing. The number of laminated ceramic green sheets is not limited to the number shown in the figure.

[0103] The ceramic green sheets 28 to 40 are respectively obtained by the following operations: an organic vehicle consisting of a binder resin and a solvent is added to the glass ceramic composition of the first embodiment of the present invention, these are mixed to obtain a ceramic slurry, the ceramic slurry is formed into a sheet by a doctor blade method, and after drying, it is punched into a specified size.

[0104] In addition, in order to provide Figure 2 The inductors L1 and L2 and the capacitor C shown are provided by wiring conductors as described below in association with the specific structures of the ceramic green sheets 28 to 40 .

[0105] A coil pattern 41 constituting a part of the inductor L1 is formed on the ceramic green sheet 30 , a lead pattern 42 extending from one end of the coil pattern 41 is formed, and a through-hole conductor 43 is provided at the other end of the coil pattern 41 .

[0106] A coil pattern 44 constituting a part of the inductor L1 is formed on the ceramic green sheet 31 , and a via-hole conductor 45 is provided at one end thereof. The other end of the coil pattern 44 is connected to the via-hole conductor 43 described above.

[0107] The ceramic green sheet 32 ​​is provided with a via-hole conductor 46 connected to the above-mentioned via-hole conductor 45 .

[0108] A capacitor pattern 47 constituting a part of the capacitor C is formed on the ceramic green sheet 33 , and lead patterns 48 and 49 extending from the capacitor pattern 47 are formed. In addition, a through-hole conductor 50 connected to the through-hole conductor 46 is provided on the ceramic green sheet 33 .

[0109] A capacitor pattern 51 constituting a part of the capacitor C is formed on the ceramic green sheet 34 , and a through-hole conductor 52 connected to the capacitor pattern 51 is provided. The capacitor pattern 51 is connected to the through-hole conductor 50 described above.

[0110] A capacitor pattern 53 constituting a part of the capacitor C is formed on the ceramic green sheet 35 , and lead patterns 54 and 55 extending from the capacitor pattern 53 are formed. In addition, a through-hole conductor 56 connected to the through-hole conductor 52 is provided on the ceramic green sheet 35 .

[0111] The ceramic green sheet 36 is provided with a via-hole conductor 57 connected to the above-mentioned via-hole conductor 56 .

[0112] A coil pattern 58 constituting a part of the inductor L2 is formed on the ceramic green sheet 37 , and a via-hole conductor 59 is provided at one end thereof. The other end of the coil pattern 58 is connected to the via-hole conductor 57 .

[0113] A coil pattern 60 constituting a part of the inductor L2 is formed on the ceramic green sheet 38, and a lead pattern 61 extending from one end of the coil pattern 60 is formed. The other end of the coil pattern 60 is connected to the above-mentioned via conductor 59.

[0114] When forming the coil patterns 41, 44, 58 and 60, the lead patterns 42, 48, 49, 54, 55 and 61, the through-hole conductors 43, 45, 46, 50, 52, 56, 57 and 59, and the capacitor patterns 47, 51 and 53 as the wiring conductors as described above, a conductive paste mainly composed of copper or silver is used, and screen printing, for example, can be applied to impart the conductive paste.

[0115] In order to obtain the green laminate 22, the ceramic green sheets 28 to 40 are Figure 3 The layers are stacked in the order shown and pressed in the thickness direction.

[0116] Thereafter, the green laminated body 22 is calcined at a temperature of 1000° C. or less, for example, 800 to 1000° C., to obtain Figure 1 Here, when the wiring conductor is mainly composed of copper, the calcination is carried out in a non-oxidizing atmosphere such as a nitrogen atmosphere or a low-oxygen atmosphere, and when the wiring conductor is mainly composed of silver, the calcination is carried out in an oxidizing atmosphere such as air. In addition, the calcination atmosphere can be a reducing atmosphere.

[0117] Next, terminal electrodes 24 to 27 are formed on the outer surface of component body 23. To form terminal electrodes 24 to 27, for example, a conductive paste mainly composed of copper or silver is applied and baked, or a thin film forming method such as vapor deposition, plating, or sputtering can be used.

[0118] As described above, the LC filter 21 can be obtained. According to the LC filter 21, the ceramic green sheets 28 to 40 are respectively made of the glass ceramic composition of the first embodiment of the present invention, that is, the ceramic green sheets 28 to 40 are respectively composed of the glass ceramic sintered bodies of the second to fourth embodiments of the present invention, so that the ε r The Qf value is high and the TCC can be reduced.

[0119] It should be noted that, in the above description, the ceramic green sheets 28 to 40 are respectively made of the glass ceramic composition of the first embodiment of the present invention, but among the ceramic green sheets 28 to 40, the ceramic green sheets 33 and 34 that directly contribute to the formation of the capacitor C are preferably made of the glass ceramic composition of the first embodiment of the present invention. That is, the ceramic green sheets 33 and 34 are preferably composed of the glass ceramic sintered bodies of the second to fourth embodiments of the present invention.

[0120] The electronic components used for the glass ceramic composition and the glass ceramic sintered body of the present invention are not limited to the LC filter 21 shown in the figure. For example, the glass ceramic composition and the glass ceramic sintered body of the present invention can also be applied to various multilayer ceramic substrates such as multilayer ceramic substrates for multi-chip modules and multilayer ceramic substrates for hybrid ICs, or various composite electronic components formed by mounting electronic components on these multilayer ceramic substrates, and various chip-type laminated electronic components such as chip-type laminated capacitors and chip-type laminated dielectric antennas.

[0121] The following contents are disclosed in this specification.

[0122] <1>

[0123] A glass-ceramic composition, comprising: an aggregate and glass containing Li2O, MgO, SrO, B2O3, SiO2 and ZnO;

[0124] Relative to 100 wt % of the above-mentioned glass-ceramic composition, it contains 9 wt % to 14 wt % of the above-mentioned glass, and contains 80 wt % to 86 wt % of ZrO2, 2 wt % to 6 wt % of CaTiO3 and 1 wt % to 4 wt % of at least one of BaCO3 and Al2O3 as the above-mentioned aggregate.

[0125] <2>

[0126] The glass-ceramic composition according to <1>, wherein in the glass,

[0127] The content of Li2O is 3 wt% to 15 wt%,

[0128] The content of MgO is 20 wt% to 50 wt%,

[0129] The content of SrO is 5 wt% to 25 wt%,

[0130] The content of B2O3 is 15 wt% to 30 wt%,

[0131] The content of SiO2 is 10 wt% to 35 wt%,

[0132] The content of ZnO is 6 wt % to 20 wt %.

[0133] <3>

[0134] An electronic component comprises a glass ceramic layer composed of a glass ceramic sintered body, wherein the glass ceramic sintered body is obtained by calcining the glass ceramic composition according to <1> or <2>.

[0135] <4>

[0136] The electronic component according to <3>, wherein the electronic component is an LC filter.

[0137] <5>

[0138] A glass ceramic sintered body comprising Zr, Ca, Ti, Ba, Li, Mg, Sr, B, Si and Zn,

[0139] The content of ZrO2 is 80 wt% to 86 wt%,

[0140] The content of CaTiO3 is 2 wt% to 6 wt%,

[0141] The content of BaO is 0.78 wt% to 3.14 wt%,

[0142] The content of Li2O is 0.3 wt% to 1.5 wt%,

[0143] The content of MgO is 2 wt% to 5 wt%,

[0144] The content of SrO is 0.5 wt% to 2.5 wt%,

[0145] The content of B2O3 is 1.5 wt% to 3 wt%,

[0146] The content of SiO2 is 1 wt% to 3.5 wt%,

[0147] The content of ZnO is 0.6 wt % to 2 wt %.

[0148] <6>

[0149] A glass ceramic sintered body comprising Zr, Ca, Ti, Al, Li, Mg, Sr, B, Si and Zn,

[0150] The content of ZrO2 is 80 wt% to 86 wt%,

[0151] The content of CaTiO3 is 2 wt% to 6 wt%,

[0152] The content of Al2O3 is 1 wt% to 4 wt%,

[0153] The content of Li2O is 0.3 wt% to 1.5 wt%,

[0154] The content of MgO is 2 wt% to 5 wt%,

[0155] The content of SrO is 0.5 wt% to 2.5 wt%,

[0156] The content of B2O3 is 1.5 wt% to 3 wt%,

[0157] The content of SiO2 is 1 wt% to 3.5 wt%,

[0158] The content of ZnO is 0.6 wt % to 2 wt %.

[0159] <7>

[0160] A glass ceramic sintered body comprising Zr, Ca, Ti, Ba, Al, Li, Mg, Sr, B, Si and Zn,

[0161] The content of ZrO2 is 80 wt% to 86 wt%,

[0162] The content of CaTiO3 is 2 wt% to 6 wt%,

[0163] The content of BaO is 0.78 wt% to 2.35 wt%,

[0164] The content of Al2O3 is 1 wt% to 3.01 wt%,

[0165] The content of Li2O is 0.3 wt% to 1.5 wt%,

[0166] The content of MgO is 2 wt% to 5 wt%,

[0167] The content of SrO is 0.5 wt% to 2.5 wt%,

[0168] The content of B2O3 is 1.5 wt% to 3 wt%,

[0169] The content of SiO2 is 1 wt% to 3.5 wt%,

[0170] The content of ZnO is 0.6 wt % to 2 wt %.

[0171] <8>

[0172] An electronic component comprising a glass ceramic layer composed of the glass ceramic sintered body according to any one of <5> to <7>.

[0173] <9>

[0174] The electronic component according to <8>, wherein the electronic component is an LC filter.

[0175] Example

[0176] Examples that more specifically disclose the glass ceramic composition and the glass ceramic sintered body of the present invention are shown below. However, the present invention is not limited to these examples.

[0177] (A) Preparation of glass powder

[0178] As the borosilicate glass powder included in the glass ceramic composition, a glass of the composition shown in the following Table 1 is prepared by the following method. First, the glass raw material powders are mixed and placed in a Pt-Rh crucible, and melted at 1650°C for more than 6 hours in an air atmosphere. Thereafter, cullet is prepared by quenching the obtained melt. Then, the cullet is coarsely crushed, placed in a container together with an organic solvent and PSZ balls (diameter: 5 mm), and mixed with a ball mill. When mixing with a ball mill, a glass powder with a center particle size of 1 to 2 μm is obtained by adjusting the crushing time. Here, "center particle size" refers to the center particle size D50 measured by a laser diffraction scattering method. It should be noted that in Table 1, the "glass symbol" marked with * is a glass powder having a composition outside the range of the glass ceramic sintered body of the present invention using the glass powder.

[0179] (B) Production of green sheets

[0180] As aggregate (filler) components, prepare 2 / g ZrO2 powder, with a specific surface area of ​​4m 2 / g of CaTiO3 powder, with a specific surface area of ​​2m 2 / g BaCO3 powder, with a specific surface area of ​​7m 2 / g of Al2O3 powder. Here, "specific surface area" refers to the value measured by the BET method. Next, the powder of the aggregate component, the glass powder and the dispersant are placed in a toluene / ethanol mixed solvent according to the ratios shown in Table 2 below, mixed with PSZ balls (diameter: 5 mm) using a ball mill, and further butyral-based binder solution and plasticizer dissolved in a toluene / ethanol mixed solvent are added and further mixed to obtain the target slurry. The slurry is formed on a carrier film with a scraper and dried to obtain two types of raw sheets with thicknesses of 15 μm and 50 μm.

[0181] (C) Preparation and evaluation of evaluation samples

[0182] The evaluation samples were prepared and evaluated by the following methods.

[0183] (1) Evaluation of sinterability and acid resistance

[0184] The samples for evaluating sinterability and acid resistance were prepared according to the following steps. 20 raw sheets of 50 μm thickness cut into 78 mm × 58 mm were stacked and hydrostatically pressed at 160 MPa to produce a pressed body. After the pressed body was cut into single pieces of 35 mm × 6 mm, it was calcined at 980 ° C for 180 minutes in a reducing atmosphere to obtain the target sample. It should be noted that the sample numbers marked with * in Table 2 are samples whose sintered bodies have a composition outside the range of the glass ceramic sintered body of the present invention.

[0185] The calcined samples were immersed in Super Check dye penetrant (manufactured by Marktec) for 1 minute, then rinsed thoroughly with running water, dried in an oven at 120°C for 120 minutes, and then visually observed to confirm the presence or absence of coloration. Samples that were confirmed to be colored were judged to be insufficiently sintered, indicated by × in Table 2, and no subsequent acid resistance evaluation was performed.

[0186] After confirming the sinterability, the weight of the sample is measured with an electronic balance. Then, the sample is placed in a 5 ml glass bottle filled with an acidic aqueous solution adjusted to pH 4 with sulfuric acid, etc., and after the lid is closed, it is placed in an oven at 73°C for 24 hours. After that, the sample is taken out, rinsed thoroughly with running water, and dried in an oven at 120°C for 120 minutes. The weight is measured again, and the dissolution rate in the acidic aqueous solution is calculated according to the following formula. Samples with a dissolution rate exceeding 0.1% are acid-resistant NG, which is indicated by × in Table 2.

[0187] Dissolution rate (%) = (weight before dissolution test - weight after dissolution test) / weight before dissolution test × 100

[0188] (2)ε r Determination of (relative dielectric constant) and Qf value (inverse of dielectric loss × frequency)

[0189] Evaluation r The samples with Qf values ​​were prepared according to the following steps. Six 50μm thick green sheets cut into 78mm×58mm were stacked and hydrostatically pressed at 160MPa to produce a pressed body. The pressed body was cut into single pieces of 42mm×35mm and calcined at 980℃ for 180 minutes in a reducing atmosphere to obtain the target sample. It should be noted that the sample number that was NG in the sinterability or acid resistance evaluation was excluded from the evaluation.

[0190] The calcined sample was used and the TE was tested according to JIS R 1641. 011 The mode resonant cavity method is used to perform ε in the millimeter wave band (25GHz) r The Q value (the inverse of dielectric loss) is measured. Two samples are measured for each grade and the average is taken as the measured value. rThe present invention does not apply to grades below 15. The Qf value is calculated according to the following formula, and the present invention does not apply to grades below 10000 GHz.

[0191] Qf value (GHz) = Q value × measurement frequency

[0192] (3) Measurement of TCC (Capacitance Change Rate)

[0193] The sample for evaluating TCC was prepared according to the following steps. A 15 μm thick sheet was cut into 47 mm × 24 mm, and an electrode paste with Cu as the main component was applied to the surface and back of the sheet by screen printing, and dried at 60°C for 30 minutes. The coating shape was a 3 mm × 3 mm opposing electrode portion with an extraction electrode portion, and 10 coatings of the same shape were formed simultaneously by one printing. It should be noted that the printing position was adjusted so that all opposing electrode portions were in the same position on the surface and back.

[0194] Next, the 50 μm thick sheet was cut into 47 mm × 24 mm, 8 sheets were stacked on one main surface side of the 15 μm thick sheet that had been printed and dried, and 8 sheets were stacked on the other main surface side, and hydrostatic pressure was pressed at 160 MPa to make a press-bonded body. Thereafter, a single sheet of 7.5 mm × 5 mm size was cut to expose the lead electrode portion at the end, and an end electrode paste with Cu as the main component was applied to the end of the single sheet to cover the lead electrode portion. Thereafter, the target sample was obtained by calcining at 980 ° C for 180 minutes in a reducing atmosphere. It should be noted that the sample number that was NG in sintering or acid resistance was excluded from the evaluation.

[0195] The TCC measurement is carried out according to the following steps. Ten sintered samples of each grade are mounted on a fixture with terminals in a thermostatic chamber, and the capacitance is measured in 5°C increments within a temperature range of -50°C to 100°C using an LCR meter. Measurement conditions: frequency 1kHz, voltage 1V, no DC bias.

[0196] Next, TCC at -40°C to 20°C and 20°C to 85°C was determined according to the following formula. Table 2 shows the maximum absolute value of TCC among 10 samples of each level, and samples with an absolute value exceeding 75 are outside the scope of the present invention.

[0197] Capacitance value at 20℃: C0

[0198] Capacitance value at -40℃: C1

[0199] Capacitance value at 85℃: C2

[0200] TCC at -40℃~20℃(ppm / ℃)=(C1-C0) / C0 / (-40-20)×1000000

[0201] TCC at 20℃~85℃(ppm / ℃)=(C2-C0) / C0 / (85-20)

[0202] ×1000000[Table 1]

[0203]

[0204] [Table 2]

[0205]

[0206] The composition ratio of the glass powder is shown in Table 1. The compositions of G8, G11, and G15 marked with * caused a phenomenon of partial crystallization of the glass, i.e., devitrification, and therefore could not be evaluated later. In addition, the compositions marked with * other than these could not satisfy the target properties when fired together with the filler.

[0207] The evaluation results of each sample are shown in Table 2. As described above, the sample numbers marked with * indicate that the sintered bodies thereof are not included in the scope of the glass ceramic sintered body of the present invention. The sample numbers other than these were confirmed to satisfy the following characteristics.

[0208] ·Sintering can be performed below 1000℃

[0209] Excellent acid resistance

[0210] ·ε r 15 or more

[0211] ·Qf value is more than 10000

[0212] ·The absolute value of TCC at -40℃~20℃ and 20℃~85℃ is less than 75ppm / ℃

[0213] The sample numbers marked with * cannot meet the above characteristics due to the following factors.

[0214] Sample No. 1: Since glass G1 containing less than 3 wt% of Li2O was used, the sinterability was low (poor).

[0215] Sample No. 4: Since glass G4 containing more than 15 wt % of Li2O was used, the acid resistance was low (poor).

[0216] Sample No. 5: Since glass G5 containing 20 wt % or less of MgO was used, the Qf value was low.

[0217] Sample No. 9: Since glass G10 containing more than 25 wt % SrO was used, the Qf value was low.

[0218] Sample No. 12: Since glass G14 containing more than 30 wt% of B2O3 was used, the acid resistance was low (poor).

[0219] Sample No. 15: Since glass G18 containing more than 35 wt % SiO2 was used, the sinterability was low (poor).

[0220] Sample No. 16: Since glass G19 containing less than 6 wt % ZnO was used, the Qf value was low.

[0221] Sample No. 19: Since glass G22 containing more than 20 wt % of ZnO was used, the acid resistance was low (poor).

[0222] Sample No. 23: Since the added amount of glass G25 was less than 9% by weight, the sinterability was low (poor).

[0223] Sample No. 27: Since the amount of glass G25 added exceeded 14% by weight, ε r Low.

[0224] Sample No. 28: Since the amount of CaTiO3 added was less than 2% by weight, the sinterability was low (poor).

[0225] Sample No. 31: Since the amount of CaTiO 3 added exceeded 6% by weight, the absolute value of TCC was high (larger on the negative side).

[0226] Sample No. 32: Since the amount of at least one of BaCO 3 and Al 2 O 3 added was less than 1 wt %, the acid resistance was low (poor).

[0227] Sample No. 36: Since the addition amount of BaCO3 exceeded 4 wt%, the Qf value was low and the TCC was high.

[0228] Sample No. 39: Since the amount of Al2O3 added exceeded 4 wt%, ε r Low.

[0229] From the above results, it is understood that the glass ceramic composition having the following composition is a glass ceramic composition having a high relative dielectric constant and Qf value of a sintered body and a small capacitance change rate.

[0230] (Preparation composition)

[0231] ZrO2 (80-86 wt%) / CaTiO3 (2-6 wt%) / at least one of BaCO3 and Al2O3 (1-4 wt%) / glass (9-14 wt%)

[0232] (Glass composition)

[0233] Li2O (3-15 wt%) / MgO (20-50 wt%) / SrO (5-25 wt%) / B2O3 (15-30 wt%) / SiO2 (10-35 wt%) / ZnO (6-20 wt%)

[0234] As an embodiment of the glass ceramic composition of the present invention, as shown in Table 2, the composition (feed composition) before calcination is recorded, but BaCO3 exists in the form of BaO after calcination. Therefore, the ratio of each component after calcination is calculated. The composition ratio corresponding to each sample number is shown in the following Table 3.

[0235] It should be noted that sometimes a portion of MgO reacts with SiO2 to become Mg2SiO4, but based on the above reaction formula (1), they are considered equivalent here.

[0236] From Tables 2 and 3, it can be seen that the fired glass ceramics (glass ceramic sintered body) having the following composition becomes a glass ceramic sintered body having a high relative dielectric constant and Qf value and a small electrostatic capacitance change rate.

[0237] (Composition of sintered body)

[0238] ZrO2 (80-86 wt%) / CaTiO3 (2-6 wt%) / BaO (0.78-3.14 wt%) / Li2O (0.3-1.5 wt%) / MgO (2-5 wt%) / SrO (0.5-2.5 wt%) / B2O3 (1.5-3 wt%) / SiO2 (1-3.5 wt%) / ZnO (0.6-2 wt%)

[0239] ZrO2 (80-86 wt%) / CaTiO3 (2-6 wt%) / Al2O3 (1-4 wt%) / Li2O (0.3-1.5 wt%) / MgO (2-5 wt%) / SrO (0.5-2.5 wt%) / B2O3 (1.5-3 wt%) / SiO2 (1-3.5 wt%) / ZnO (0.6-2 wt%)

[0240] ZrO2 (80-86 wt%) / CaTiO3 (2-6 wt%) / BaO (0.78-2.35 wt%) / Al2O3 (1-3.01 wt%) / Li2O (0.3-1.5 wt%) / MgO (2-5 wt%) / SrO (0.5-2.5 wt%) / B2O3 (1.5-3 wt%) / SiO2 (1-3.5 wt%) / ZnO (0.6-2 wt%)

[0241] [Table 3]

[0242]

[0243] Explanation of symbols

[0244] 43, 45, 46, 50, 52, 56, 57, 59 through-hole conductors

[0245] 21LC filter

[0246] 23 parts body

[0247] 24~27 terminal electrodes

[0248] 28~40 ceramic green sheets

[0249] 41, 44, 58, 60 coil patterns

[0250] 42, 48, 49, 54, 55, 61 lead patterns

[0251] 47, 51, 53 capacitor patterns

Claims

1. A glass-ceramic composition comprising: an aggregate and a glass containing Li2O, MgO, SrO, B2O3, SiO2 and ZnO; Relative to 100 wt % of the glass-ceramic composition, it contains 9 wt % to 14 wt % of the glass, and contains 80 wt % to 86 wt % of ZrO2, 2 wt % to 6 wt % of CaTiO3 and 1 wt % to 4 wt % of at least one of BaCO3 and Al2O3 as the aggregate.

2. The glass-ceramic composition according to claim 1, wherein In the glass, The content of Li2O is 3 wt% to 15 wt%, The content of MgO is 20 wt% to 50 wt%, The content of SrO is 5 wt% to 25 wt%, The content of B2O3 is 15 wt% to 30 wt%, The content of SiO2 is 10 wt% to 35 wt%, The content of ZnO is 6 wt % to 20 wt %. 3 . An electronic component comprising a glass ceramic layer composed of a glass ceramic sintered body obtained by calcining the glass ceramic composition according to claim 1 or 2.

4. The electronic component according to claim 3, wherein The electronic component is an LC filter.

5. A glass ceramic sintered body comprising Zr, Ca, Ti, Ba, Li, Mg, Sr, B, Si and Zn, The content of ZrO2 is 80 wt% to 86 wt%, The content of CaTiO3 is 2 wt% to 6 wt%, The content of BaO is 0.78 wt% to 3.14 wt%, The content of Li2O is 0.3 wt% to 1.5 wt%, The content of MgO is 2 wt% to 5 wt%, The content of SrO is 0.5 wt% to 2.5 wt%, The content of B2O3 is 1.5 wt% to 3 wt%, The content of SiO2 is 1 wt% to 3.5 wt%, The content of ZnO is 0.6 wt % to 2 wt %.

6. A glass ceramic sintered body comprising Zr, Ca, Ti, Al, Li, Mg, Sr, B, Si and Zn, The content of ZrO2 is 80 wt% to 86 wt%, The content of CaTiO3 is 2 wt% to 6 wt%, The content of Al2O3 is 1 wt% to 4 wt%, The content of Li2O is 0.3 wt% to 1.5 wt%, The content of MgO is 2 wt% to 5 wt%, The content of SrO is 0.5 wt% to 2.5 wt%, The content of B2O3 is 1.5 wt% to 3 wt%, The content of SiO2 is 1 wt% to 3.5 wt%, The content of ZnO is 0.6 wt % to 2 wt %.

7. A glass ceramic sintered body comprising Zr, Ca, Ti, Ba, Al, Li, Mg, Sr, B, Si and Zn, The content of ZrO2 is 80 wt% to 86 wt%, The content of CaTiO3 is 2 wt% to 6 wt%, The content of BaO is 0.78 wt% to 2.35 wt%, The content of Al2O3 is 1 wt% to 3.01 wt%, The content of Li2O is 0.3 wt% to 1.5 wt%, The content of MgO is 2 wt% to 5 wt%, The content of SrO is 0.5 wt% to 2.5 wt%, The content of B2O3 is 1.5 wt% to 3 wt%, The content of SiO2 is 1 wt% to 3.5 wt%, The content of ZnO is 0.6 wt % to 2 wt %. 8 . An electronic component comprising a glass ceramic layer composed of the glass ceramic sintered body according to claim 5 .

9. The electronic component according to claim 8, wherein The electronic component is an LC filter.

Citation Information

Patent Citations

  • Glass ceramic composition, glass ceramic sinter and laminated type ceramic electronic component

    WO2009113475A1